Coffee Waste as a Potential Adsorbent for Peat Water Treatment - Rahma Amalia; Sarah Fiebrina Heraningsih; Oki Alfernando; Sri Mundarti; Muhammad Haviz; Nadia Elvina; Sonia Nizal Putri; Resi Lisma Kinasih; Asmara; Yuzi Chantika Pratama; Ahmad Fadhilah Ashidiqie (CHEESA: Chemical Engineering Research Articles, 2025)
Peat water is characterized by high acidity, turbidity, and poor sensory qualities, which limit its usability. This study evaluated the effectiveness of thermally activated coffee waste adsorbent (CWA) for peat water treatment. CWA was prepared by heating coffee waste at 250°C, followed by washing and drying at 60°C. Batch adsorption experiments were conducted using 13 g of CWA in 200 mL of peat water at 30°C, stirred at 150 rpm for 30 minutes. The results revealed significant improvements in water quality: pH increased from 3.85 to 4.62; turbidity was reduced by 99.37% (from 75 to 0.47 NTU); conductivity decreased by 30.7% (from 424 to 294 ?S/cm); and total dissolved solids (TDS) dropped by 93.3% (from 208 to 14 ppm). The Langmuir isotherm model (R² = 0.7297) provided a better fit than the Freundlich model (R² = 0.5845), indicating monolayer adsorption behavior with a maximum capacity of 0.1634 mg/g and a favorable separation factor (RL = 0.0057). Sensory evaluation confirmed enhanced color and odor. These findings support the use of CWA as a sustainable and low-cost adsorbent for improving peat water quality.